Public Pharmacies on the Territory of Bosnia and Herzegovina Over the Austro-Hungarian Rule - Marković-Peković, Vanda (Scripta Medica, 2022)
Background/Aim: With the adoption of legislation over the Austro-Hungarian rule (1878–1918) apothecary in Bosnia and Herzegovina (B&H) became a regulated profession, which enabled the arrival of graduated pharmacists. The aim of the paper was to present in which towns on the B&H territory public pharmacies were opened over this period and their owners. Methods: A retrospective and descriptive research was conducted at the Archives of the Republic of Srpska, the Museum of the Republic of Srpska and the Archives of Bosnia and Herzegovina. The method of the qualitative secondary data analysis was applied. Results: With the arrival of Masters of Pharmacy from all parts of the Austro-Hungary, an increasing number of public pharmacies began to open. Concessions for the opening pharmacies were initially granted to foreigners and among the settlers, pharmacists there were mostly Czechs, Croats, Poles, Hungarians, Slovaks, who completed pharmacy studies at universities in Vienna, Zagreb, Prague, Lviv, Graz, Innsbruck, Krakow. In the beginning, there were no locally educated pharmacists and the first appeared at the end of the 19th and the beginning of the 20th century. During this period at least one pharmacy was opened in many towns, two worked in Banja Luka, Mostar, Tuzla and Bijeljina and seven in Sarajevo. In the first years, each pharmacy was staffed by only one pharmacist and over time there were more pharmacy staff in the pharmacies. Twenty years after the occupation, public pharmacies owned by Masters of Pharmacy were opened in thirty three towns around B&H and in 1918 there were forty eight public pharmacies in thirty eight towns. Conclusion: The number of public pharmacies and qualified pharmacy staff in B&H increased over the Austro-Hungarian rule from 1878 to 1918, which contributed to the improvement of the profession, health and social conditions in the country during this period.